Cost-Effectiveness of Point-of-Care A1C Tests in a Primary Care Setting - Rosa, Lorena de Sousa; Mistro, Sóstenes; Oliveira, Marcio Galvão; Kochergin, Clavdia Nickolaevna; Cortes, Mateus Lopes; Medeiros, Danielle Souto de; Soares, Daniela Arruda; Louzado, José Andrade; Silva, Kelle Oliveira; Bezerra, Vanessa Moraes; Amorim, Welma Wildes; Barone, Mark; et al. (Frontiers in Pharmacology, 2021)
Objective: We evaluated the cost-effectiveness of the point-of-care A1c test device versus the traditional laboratory dosage in a primary care setting for people living with type 2 diabetes. Research Design and Methods: The economic model was based on data from the HealthRise project, in which a group of interventions was implemented to improve diabetes and hypertension control in the primary care network od the urban area of a Brazilian municipality. A POC-A1c device was provided to be used directly in a primary care unit, and for a period of 18 months, 288 patients were included in the point-of-care group, and 1,102 were included in the comparison group. Results: The results indicated that the POC-A1c device used in the primary care unit was a cost-effective alternative, which improved access to A1c tests and resulted in an increased rate of the early control of blood glucose. Conclusions: This study showed that using POC-A1c devices in primary care settings is a cost-effective alternative for monitoring glycated hemoglobin A1c as a marker of blood glucose control in people living with type 2 diabetes. Compared to a centralized laboratory test, the POC-A1c device used in a healthcare unit increased the early control of type 2 diabetes and reduced costs for DM-related outcomes.